The Effect Of Occupational Safety And Health (K3) On The Productivity Of Rubber Tapping Workers At PT. London Sumatra (Lonsum) Indonesia Tbk. Balombessie Bulukumba Regency - Aslinda Anwar; Dg. Maklassa; Nurinaya, Nurinaya (CV. AFDIFAL MAJU BERKAH, 2024)
The aim of this research is to find out whether the implementation of the occupational safety and health (K3) program has an effect on increasing the productivity of rubber tapping workers at PT. Lonsum Indonesia Tbk. Balombessie, Bulukumba Regency. The type of research used is quantitative, namely a research method that uses numerical data with a sample size of 52 respondents and uses data analysis techniques: validity and reliability tests, classical assumption tests, simple regression analysis. Based on the results of research conducted at the data collection, data management and data analysis stages regarding the influence of occupational safety and health (K3) on the productivity of rubber tapping workers at PT. London Sumatra (Lonsum) Indonesia Tbk. Balombessie, Bulukumba Regency, it can be concluded that the implementation of the occupational safety and health program has a positive and significant effect on the productivity of rubber tapping workers at PT. London Sumatra (Lonsum) Indonesia Tbk. Balombessie, Bulukumba Regency.